Changing perspective of agricultural extension - Kokate, K D (Indian Farming, 2015)
Agricultural Knowledge Management is gaining centre stage of agricultural extension system to avail the benefits of information revolution. It was observed that extension has to once again reorganize as a service for providing information, advice and education, rather than technology transfer. For efficient agricultural communication, KVKs would focus on knowledge and technology management. This would result in technology application and transfer for maximizing enterprise output.